Pelatihan Penerapan E-Modul Berbasis Canva Untuk Meningkatkan Kompetensi Literasi Digital Guru Sekolah Dasar Di Kota Kupang - Meilani, Dian; Muhsam, Julhidayat; Nurlailah; Uslan; Nuriyah; Hasyda, Suryadin; Letasado, Muhamad Rusadi (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
This E-Module implementation training aims to provide solutions to problems faced by partner schools as well as providing training in improving digital literacy competencies based on applications that are easy to use in learning. This application is in the form of a Canva-based e-module that is easy for students to use. This training and mentoring was carried out at SD Inpres Oeba 2 Kupang. The method for implementing this training is through discussions with all lecturer teams and partners and produces E-Modules that can be used by students effectively